Implementation of the overall equipment cost loss (OECL) methodology for comparison with overall equipment effectiveness (OEE) - Ratapol Wudhikarn (2018)
© Emerald Group Publishing Limited. Purpose - The purpose of this paper is to describe the overall equipment cost loss (OECL) methodology and an implementation of this methodology, to compare the outcomes of OECL with those of overall equipment effectiveness (OEE), and finally to identify the benefits offered by this new methodology. Design/methodology/approach - The proposed methodology, OECL, combines six large loss models and a financial model in the performance evaluation of equipment. The six large losses are converted into monetary units. OECL is a new way of evaluating equipment performance that differs from the original OEE methodology and overcomes some of the limitations of OEE. This new methodology can be used to rank problematic machines by accounting for production elements together with finance elements. Findings - The OECL and OEE methodologies rank problematic machines differently. Research limitations/implications - Efforts were made in this research to identify factors affecting OECL outcomes, but it was found that it was not possible to apply OECL to all scenarios. Practical implications - The OECL model can be implemented in a real manufacturing company to help decision-makers better determine the magnitudes of equipment problems and rank problematic pieces of equipment appropriately. Originality/value - This OECL method is able to overcome some of OEE's weaknesses. It can properly prioritise problematic machines by considering both cost and losses.